SPPQT Program Evaluation for Food Access and Food Choice for the Elderly in the SPPQT Empowerment Areas - Beathrix Finelya; Theresia Pratiwi; Arwyn Weynand Nusawakan (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2022)
The increasing number of the elderly population also causes an increase in various diseases, including malnutrition. To overcome this, the food choice for the elderly in their environment must be considered. Moreover, the elderly tend to experience decreased access to nutrition and healthy food because of their physical limitations. In 1999, Serikat Paguyuban Petani Qaryah Thayyibah (SPPQT) was formed for farmer groups to connect its members and distribute food through its empowerment program. This study aims to evaluate the role of SPPQT’s empowerment for the elderly to increase the food supply, which impacts access and food choice for the elderly. This study involved five participants. The result is that SPPQT has no responsibility for meeting food needs, including food selection and access for all farmers, including the elderly. The SPPQT program is only limited to farmer empowerment involving elderly farmers. However, access to food for all farmers, including the elderly farmers, is good. Yet, the selection of food for elderly farmers is not yet varied. Therefore, it is recommended that SPPQT should develop an empowerment program for the provision of food for older farmers and an increase in knowledge capacity related to food supply through access and selection of food for SPPQT’s elderly assisted groups.